2014
DOI: 10.1155/2014/978034
|View full text |Cite
|
Sign up to set email alerts
|

Panaxatriol Saponins Attenuated Oxygen-Glucose Deprivation Injury in PC12 Cells via Activation of PI3K/Akt and Nrf2 Signaling Pathway

Abstract: Panaxatriol saponins (PTS), the main components extracted from Panax notoginseng, have been shown to be efficacious in the prevention and treatment of cerebrovascular diseases in China. NF-E2-related factor 2 (Nrf2), a transcription factor regulating antioxidant and cytoprotective responses to oxidative stress, has received particular attention as a molecular target for pharmacological intervention of ischemic diseases. The aim of this study was to characterize the effect of PTS on the activation of Nrf2 signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…The results indicated that PTS at the concentrations ranging from 0.03 to 2 mg/ml significantly ameliorated the cell growth inhibition and apoptosis induced by 6-OHDA in PC12 cells (Fig. 1B and C), which was in line with the previous reports that PTS protected PC12 cells against oxygen-glucose deprivation reperfusion- and 1-methyl-4-phenylpyridinium ion-induced cell damage1819. However, relatively high concentration of PTS (4 mg/ml) did not show neuroprotective activity but enhanced the cytotoxicity of 6-OHDA (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results indicated that PTS at the concentrations ranging from 0.03 to 2 mg/ml significantly ameliorated the cell growth inhibition and apoptosis induced by 6-OHDA in PC12 cells (Fig. 1B and C), which was in line with the previous reports that PTS protected PC12 cells against oxygen-glucose deprivation reperfusion- and 1-methyl-4-phenylpyridinium ion-induced cell damage1819. However, relatively high concentration of PTS (4 mg/ml) did not show neuroprotective activity but enhanced the cytotoxicity of 6-OHDA (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…. PTS have been reported to exhibit neuroprotective effects on oxygen-glucose deprivation-reperfusion induced PC12 cell death18 and 1-methyl-4-phenylpyridinium ion-induced neurotoxicity in mice19. However, the cellular and molecular mechanisms remain to be elucidated.…”
mentioning
confidence: 99%
“…19) In brief, PC12 cells were first incubated in glucose-free DMEM and subsequently transferred into a Tri-Gas incubator (Heal Force, HF100) with 1% O 2 , 94% N 2 and 5% CO 2 for 9 h at 37°C. Sham OGD cultures were maintained in a normal oxygenated DMEM.…”
Section: Methodsmentioning
confidence: 99%
“…Panaxatriol saponins may activate endogenous cytoprotective mechanism against oxygen-Glc deprivation-reperfusion-induced oxidative injury via the activation of PI3K/AKT and Nrf2 signaling pathway (Huang et al, 2014). Panaxatriol saponins may activate endogenous cytoprotective mechanism against oxygen-Glc deprivation-reperfusion-induced oxidative injury via the activation of PI3K/AKT and Nrf2 signaling pathway (Huang et al, 2014).…”
Section: Antioxidant and Anti-inflammatory Effectsmentioning
confidence: 99%